Aberration characterization of x-ray optics using multi-modal ptychography and a partially coherent source - Moxham, TEJ; Laundy, D; Dhamgaye, V; Fox, OJL; Sawhney, K; Korsunsky, AM (American Institute of Physics, 2021)
Ptychography is a scanning coherent diffraction imaging technique that provides high-resolution imaging and complete spatial information of the complex probe and object transmission function. The wavefront error caused by aberrated optics has previously been recovered using ptychography when a highly coherent source is used, but has not been demonstrated with partial coherence due to the multi-modal probe required. Here, we demonstrate that partial coherence can be accounted for in ptychographic reconstructions using the multi-modal approach and assuming that decoherence arises from either the probe or the object. This equivalence recovers coherent (or single state) reconstructions of both the probe and the object even in the presence of partial coherence. We demonstrate this experimentally by using hard x-ray ptychography with a partially coherent source to image a Siemens star test object and to also recover the wavefront error from an aberrated beryllium compound refractive lens. The source properties and resolving capabilities are analyzed, and the wavefront error results are compared with another at-wavelength metrology technique. Our work demonstrates the capability of ptychography to provide high-resolution imaging and optics characterization even in the presence of partial coherence.